2007
DOI: 10.1016/j.yjmcc.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Survival and maturation of human embryonic stem cell-derived cardiomyocytes in rat hearts

Abstract: Purpose-Human embryonic stem cell (hESC)-derived cardiomyocytes are a promising cell source for cardiac repair. Whether these cells can be transported long distance, survive, and mature in hearts subjected to ischemia/reperfusion with minimal infarction is unknown. Taking advantage of a constitutively GFP-expressing hESC line we investigated whether hESC-derived cardiomyocytes could be shipped and subsequently form grafts when transplanted into the left ventricular wall of athymic nude rats subjected to ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(82 citation statements)
references
References 57 publications
(34 reference statements)
1
80
0
1
Order By: Relevance
“…It remains to be elucidated whether the described bidirectional effects on connexin43 and N-cadherin expression in heterotypic cell pairs are the result of juxtacrine (cell contact mediated) and/or short-range paracrine signaling from the abutting cells. Furthermore, although a diffuse (dotted) pattern of connexin43 and N-cadherin has been previously reported in infarct border zones (30,40) and regions with implanted cells (10,46), further studies are warranted to investigate the precise distribution of coupling proteins at heterocellular interfaces within the heart.…”
Section: Discussionmentioning
confidence: 94%
“…It remains to be elucidated whether the described bidirectional effects on connexin43 and N-cadherin expression in heterotypic cell pairs are the result of juxtacrine (cell contact mediated) and/or short-range paracrine signaling from the abutting cells. Furthermore, although a diffuse (dotted) pattern of connexin43 and N-cadherin has been previously reported in infarct border zones (30,40) and regions with implanted cells (10,46), further studies are warranted to investigate the precise distribution of coupling proteins at heterocellular interfaces within the heart.…”
Section: Discussionmentioning
confidence: 94%
“…The mES and hES cell derived CMs form stable myocardial grafts in a variety of immuno-compromised animal hosts (Dai et al, 2007;Kehat et al, 2004;Klug et al, 1996;Laflamme et al, 2005) Moreover, hES derived CMs have been shown to restore function in cardiac damaged models. They improve contractility for the infarcted murine heart and provide pacing activity in pig hearts that have undergone atrioventricular node ablation (Cai et al, 2007a;Kehat et al, 2004).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…This is perhaps not surprising, since the cells may represent the equivalent of early fetal cardiomyocytes, so it will be important to investigate the potential for further maturation in vitro. Nevertheless, several groups have shown that the cells survive when transplanted into rodent models and can improve function in the infracted rat heart [27,55,56], although further maturation or integration of the cells may be needed for long-term survival and successful therapy [57].…”
Section: Human Es-derived Cardiomyocytes and Ipsmentioning
confidence: 99%